Oligomeganephronia: Case report and literature review - Yang Xiang-Dong; Shi Weiwei; Li Dengren; Peng Tao (Srpski Arhiv za Celokupno Lekarstvo, 2014)
Introduction. Oligomeganephronia (OMN) is one of rare congenital kidney disease. The number of nephrons reduces and the volume of glomerulus increases. The incidence of OMN is uncertain because it is difficult to diagnose. There are no any special clinical manifestations of OMN. Renal pathology is the only way to diagnose OMN, so missed diagnosis always happens without renal pathology. Case Outline. A 26-year-old male was diagnosed OMN associated with proteinuria and increased serum creatinine. The size of both kidneys on ultrasound was smaller than normal. Pathological features involved a reduced number of greatly enlarged glomeruli indicating OMN. Conclusion. OMN is a rare disease and it has been rarely reported. The exact mechanism is not clear. The diagnosis mainly depends on pathological findings. For patients with OMN, proteinuria and renal dysfunction are often the main cause to visit a doctor. Early diagnosis is important.